Pemeriksaan Kesehatan Mata untuk Anak dengan Down Syndrome dalam Peringatan Bulan Peduli Down Syndrome 2023 oleh PIK POTADS Jawa Timur - Joko Irawan; Yasmin Yasmin; Sony Agung Santoso (CV. ALIM'SPUBLISHING, 2023)
This study aims to determine the prevalence of refractive errors in children with Down Syndrome in eye examination activities carried out during Down Syndrome Awareness Month 2023 by the East Java Association of Parents of Children with Down Syndrome (PIK POTADS). A total of 30 children with Down Syndrome underwent eye examinations, and the results showed that 18 children (72%) had myopia, 7 children (28%) had astigmatism, and 5 children were indicated to require further referral to a pediatric ophthalmologist. These results indicate that children with Down Syndrome have a high risk of experiencing refractive errors, so regular eye examinations and medical follow-up are needed.